The Case for Specific Performance as the Primary Remedy for Breach of Contract in New Zealand - Cuncannon, Fionnghuala (Victoria University of Wellington Law Review, 2004)
This article examines the appropriateness of damages as the primary remedy for breach of contract in New Zealand. It argues that the civil law approach to contractual remedies, which gives primacy to performance of the obligation, is superior to New Zealand's common law position, which merely seeks to replace the right to performance with an award of damages. The importance of both the normative and practical impact of the remedial framework is examined in order to demonstrate that specific performance is better able to facilitate commercial endeavours. The three justifications for the primacy of damages in the common law (the historical development, the economic theory of efficient breach, and the concern that specific performance will overburden the administration of justice) are examined but rejected as adequate justification for the common law position. It contends that specific performance should be the primary remedy because it is more consistent with the principles that underlie the law of contract. It also contends that specific performance is more practical because it reduces conflict and promotes efficiency. The recommendation is that any change should be through appropriate legislation.